Effect of different vulcanization system and filler loading on structure and mechanical properties of natural rubber foam - Mogan A/L Mahadevan (School of Polymer Engineering, University Malaysia Perlis, 2016)
This study was conducted to identify the effect of different vulcanization system and tyre dust loading on structure and mechanical properties of natural rubber foam. The natural rubber foam was prepared by mixing the formulation ingredients consist of two variables such as concentration of sulphur and concentration of tyre dust. The rubber was masticated and all the compounding ingredients were mixed using two rolls mill. Partial vulcanization was carried out using compression molding followed by simultaneous vulcanization and foaming in an air-circulating oven. Two types of testing was done upon natural rubber foam were physical testing and mechanical testing. For physical testing, morphology of the foam, relative foam density and crosslink density was found. For cell morphology, the cell size and cell wall thickness was observed by using Dino-Lite Digital Microscope. For mechanical testing, compression stress was determined by using Instron machine. The results showed that the relative foam density increases with increase in the concentration of sulphur and also tyre dust. It is also found that the cell wall thickness increases as concentration of sulphur increases but remains almost constant with incorporation of tyre dust. Increase in cell wall thickness was then found to increase the compression strength of the natural rubber foam.